2
$\begingroup$

I have the integral, $$I=\int_{-1}^1 dx P'_m(x) P'_n(x).$$ I tried using $$P_m'(x)=-(m+1)\frac{xP_m(x)-P_{m+1}(x)}{x^2-1},$$ but that yields, $$I=\int_{-1}^1\bigg(\frac{x^2P_mP_n}{(x^2-1)^2}+\frac{P_{m+1}P_{n+1}}{(x^2-1)^2}-\frac{xP_mP_{n+1}}{(x^2-1)^2}-\frac{xP_{m+1}P_n}{(x^2-1)^2}\bigg),$$ which did not seem particularly convenient to me either. Alternatively, using integration by parts, along with $(1-x^2)P''_m-2xP'_m+m(m+1)P_m=0$ $$I=P'_mP_n\big\vert_{-1}^1-\int_{-1}^1 dx P_n P''_m=P'_mP_n\big\vert_{-1}^1-\int_{-1}^1\bigg(\frac{2xP_nP'_m}{1-x^2}-m(m+1)\frac{P_nP_m}{1-x^2}\bigg).$$ Stuck either way. Lastly, I tried using the associated Legendre polynomials to cast the original integral as, $$\int_{-1}^1 dx\frac{P_m^1P_n^1}{1-x^2},$$ which I could not find.

I guess the only way out might be to use the Rodrigues formula and churn through all the terms?

Addendum: A brute force evaluation on Mathematica, of both the last expression in terms of the associated Legendre functions, and the initial expression, seems to yield $$I=\int_{-1}^1 dx P'_m(x) P'_n(x)=\int_{-1}^1 dx\frac{P_m^1P_n^1}{1-x^2}=\begin{cases}&k(k+1),\quad k=\mathrm{min}(m,n);\quad m,n \text{ both odd or even}\\&0;\quad \text{otherwise}\end{cases}$$

$\endgroup$
1
$\begingroup$

After integration by parts, it's much easier to use orthogonality. If $m\leqslant n$ (say), then $$\int_{-1}^1 P_m'(x)P_n'(x)\,dx=P_m'(x)P_n(x)\Big|_{-1}^1-\int_{-1}^1 P_m''(x)P_n(x)\,dx;$$ the last integral is $\color{red}{0}$ because of orthogonality of $P_n$ to any polynomial of degree $<n$, and $$P_n(1)=(-1)^nP_n(-1)=1,\quad P_m'(1)=(-1)^{m-1}P_m'(-1)=m(m+1)/2.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.